Evaluation of SBMU Residents' Knowledge and Use of Evidence-Based Medical Databases and Concepts - Arefeh Kalavani; Maryam Kazerani; Maryam Shekofteh (Tehran University of Medical Sciences, 2018)
Background and Aim: With the development of the Internet and databases and the increasing need to institutionalize evidence-based medicine, physicianschr('39') awareness and use of evidence-based medical databases and concepts are considered to be necessary. Therefore, the aim of this study is to evaluate the knowledge and use of evidence-based medical concepts and databases among residents of Shahid Beheshti University of Medical Sciences (SBMU). Materials and Methods: The present study is an applied and descriptive research. The population of this study comprised 192 SBMU residents in 2016. A questionnaire was used for data collection and SPSS software was applied for data analysis. Results: The findings showed that residents obtained 2.99 for knowledge and 2.73 for the use of evidence-based medical databases out of a total average of 5 points, which indicates that their knowledge and practical use of evidence-based medical databases are moderate. Databases about which residents have the highest knowledge and practical use are UpToDate, PubMed Clinical Queries, and  Cochrane, respectively.  Conclusion: The majority of residents at Shahid Beheshti University of Medical Sciences do not have sufficient awareness about databases and concepts of evidence-based medicine; in fact, most of the resources that are used to answer their information needs are non-evidence-based resources. Therefore, planning to accept evidence-based medicine and databases and teach them to residents is essential.